PENYULUHANPENINGKATANKESADARANMASYARAKATTERHADAPTANGGAPBENCANA (KHUSUSNYALONGSOR) - Yulianto Purwono Prihatmaji (Asian Journal of Innovation and Entrepreneurship, 2013)
Geographical location Padukuhan Nglambur average hilly cause groundwater inthe area is prone to landslides. The importance of awareness of every citizen to knowabout the emergency response (especially landslides) is considered very important, so ifat any time a landslide, then the expectation of every citizen to know what to do, atleast it can reduce the consequences of disasters (landslides) the , Basically in PadukuhanNglambur own existing community disaster response, just that he had not held an event,so I took the initiative to refresh the knowledge of emergency response to landslideswith this program. The hope after the program is running the public can find out moreabout how the emergency response (landslides), particularly at the family level. Theprogram is implemented in the form of socialization and community Q & A with door todoor. With this event the general public can go back to refresh the knowledge ofemergency response and disaster preparedness landslides, especially in the level of headof the family (home).